P468 Association of uncontrolled disease with quality of life and healthcare resource utilisation in Ulcerative Colitis patients treated with advanced therapy in the United States. (30th January 2023) - Igho-Osagie, E; Knight, H; Barlow, S; Harvey, N; Khandker, R
Abstract: Background: Advanced therapies (AT; i.e., biologics, biosimilars, Janus kinase inhibitors) are used to treat patients with moderate to severe ulcerative colitis (UC) after inadequate response to conventional treatments; yet some patients continue to have uncontrolled disease. We examined the association between uncontrolled UC and health-related quality of life (HRQoL) and healthcare resource utilisation (HCRU) in a real-world clinical setting. Methods: The analysis was conducted using secondary data from the Adelphi UC Disease Specific Programme™, 1 a cross-sectional, retrospective survey of gastroenterologists and patients, from January 2020-March 2021. Gastroenterologists provided clinical characteristics and HCRU information for 5-7 consecutive UC patients, while EuroQol-5-dimensions (EQ-5D), EQ-visual analogue scale (EQ-VAS), short inflammatory bowel disease questionnaire (SIBDQ) and work productivity and impairment questionnaire (WPAI) were patient-administered to capture HRQoL status. Patients receiving AT for ≥6 weeks were classified as uncontrolled if: physician assessment was currently moderate or severe, they had ≥2 flares in the last 12 months, or currently had ≥3 symptoms. Patient characteristics and outcomes were compared using T-test and Fisher's exact test. Multivariable linear regressions estimating the association between UC control status and HRQoL were adjusted for age, ethnicity, disease duration and severity at diagnosis. Results: Of the 236 patients included in the sample, 57.6% had uncontrolled disease and were likely to be non-White (27.9% v 14.0% controlled; p=0.01). Although healthcare provider consultations were similar in both groups, uncontrolled patients had more radiological imaging (mean 1.9 v 1.3, p<0.01), endoscopies (mean 0.6 v 0.3, p<0.01) and hospitalisations (mean 0.2 v 0.1, p=0.01) in the last 12 months compared to controlled patients. Uncontrolled patients reported significantly lower (worse) total and subdomain SIBDQ scores (total: 47.2 v 59.6; systemic symptoms: 4.8 v 5.9; bowel symptoms: 4.7 v 6.1; emotional function: 4.6 v 5.6; social function: 4.8 v 6.2; all p<0.01; Table 3). EQ-5D (0.85 v 0.92, p<0.01), EQ-VAS scores (76.3 v 86.1, p<0.01) and activity impairment (29.2 v 16.7, p<0.01) were significantly worse in the uncontrolled group. Conclusion: A substantial number of UC patients continue to have uncontrolled disease and high unmet need despite AT use. These patients experience poorer HRQoL and contribute a significant burden on healthcare resources. Study findings highlight the need for innovative therapeutic options that would further reduce disease burden for patients and the healthcare system. 1. Anderson P et al . Curr Med Res Opin 2008;24;3063–72.